Linking bodily, environmental and mental states in the self—A three-level model based on a meta-analysis. (August 2020) - Qin, Pengmin; Wang, Mingxia; Northoff, Georg
Highlights: Identifies a three-level gradient neural mechanism in self-processing. Establishes the crucial role of insula and interoceptive signals in self-processing. Demonstrates the role played by the TPJ and AMPFC in bridging the bodily- and mental-self. Highlights the importance of sensory signals in even non-bodily-self processing. Summarizes the major neural correlates underlying various self-processing manipulations. Abstract: Current researchers mostly agree that the self consists of both bodily and non-bodily environmental information. The neural mechanism underlying the integration of this information remains unclear. In this study, we propose a neural model subdividing self-processing into three intimately connected levels with different extension: Interoceptive-processing, Exteroceptive-processing and Mental-self-processing. We applied ALE meta-analyses on neuroimaging studies to analyze their neural patterns. Our results show common involvement of insula across all three levels including differentiation of self and familiarity. Common activities in Exteroceptive- and Mental-self-processing were found in the anteromedial prefrontal cortex (AMPFC) and the temporal parietal junction (TPJ), suggesting that the two regions likely serve basic functions in differentiation and integration of self-other information. Finally, Mental-self-processing involves extensive regions such as the cingulate cortex and medial prefrontal cortex, in addition to the insula, AMPFC and TPJ, which could specialize in adding self-relatedness to environment information. We conclude that there is a gradient organization in self-processing, through which body-environment information is integrated for the self via propagation from Interoceptive-processing to Mental-self-processing.